What’s is the answer
![Whats is the answer class=](https://us-static.z-dn.net/files/d28/19322f3fd45f98ec3a34dd12835d4d20.png)
When you are multiplying an exponent directly into a number/variable with an exponent, you multiply the exponents together.
For example:
[tex](x^{2} )^{3} = x^6[/tex]
[tex](x^{3} )^5=x^{15}[/tex]
When you are multiplying a variable with an exponent by another variable with an exponent, you add the exponents together.
For example:
[tex](x^{2} )(x^{3})=x^{5}[/tex]
[tex](x^{1} )(x^{2})=x^{3}[/tex]
[tex](\frac{(x^{-3})(y^{2})}{(x^{4})(y^{6})} )^{3}=\frac{(x^{-9})(y^{6})}{(x^{12})(y^{18})}[/tex]
You multiply 3 into each exponent in the numerator and the denominator
[tex]\frac{(x^{-9})(y^{6})}{(x^{12})(y^{18})}= \frac{y^{6}}{(x^{9})(x^{12})(y^{18})}[/tex]
When you have a negative exponent, you move it to the other side of the fraction to make the exponent positive.
[tex]\frac{y^{6}}{(x^{21})(y^{18})} = \frac{1}{(x^{21})(y^{12})}[/tex]
When you have something like this:
[tex]\frac{x^{2}}{x^5}[/tex]
You subtract the exponents together, so:
[tex]\frac{x^2}{x^5} = x^{2-5} = x^{-3} = \frac{1}{x^3}[/tex]
Your answer is the second option